Surface engineering of 3D spinel Zn3V2O8 wrapped on sulfur doped graphitic nitride composites: Investigation on the dual role of electrocatalyst for simultaneous detection of antibiotic drugs in biological fluids. (1st August 2022) - Rajaji, Umamaheswari; Govindasamy, Mani; Sha, Rinky; Alshgari, Razan A.; Juang, Ruey-Shin; Liu, Ting-Yu
Abstract: Sensitive detection of antibiotics is one of the crucial research areas at present. The present work describes the simple deep eutectic solvent based hydrothermal methods for the synthesis of 3D metal vanadate's; T3 V2 O8 (T = Cu, Ni and Zn). Further, these 3D T3 V2 O8 have been anchored with sulfur doped carbon nitride (SGN). The morphological characterization confirms the formation of rhombus, rice and flower like structures of CVO, NVO and ZVO, respectively. All the three nanocomposites have been used to modify laser-induced graphene electrodes (LGE) and been evaluated for the detection of two antibiotics; nitrofurantoin (NFT) and chloramphenicol (CAP). The electrochemical performance of antibiotics has been studied using cyclic voltammetry (CV), electrochemical impedance spectroscopy (EIS) and differential pulse voltammetry (DPV) techniques. Among three composites ZVO/SGN showed enhanced selectivity and sensitivity compared to CVO/SGN and NVO/SGN. Using DPV method, the sensitivity of the ZVO/SGN/LGE sensor achieved for the detection of CAP and NFT is 55.71 μA μM −1 cm −2 and 23.06 μA μM −1 cm −2 respectively. Using this ZVO/SGN nanomaterial-enhanced multiplex electrochemical sensing system, simultaneous detection of CAP and NFT was realized with a limit of detection of 1.5 nM and 2.4 nM, respectively. To validate the use of the sensor in real sample applications, detection experiments were performed in bovine serum and urine. The ZVO/SGN modified LGE shows enhanced sensitivity as well as selectivity for the simultaneous detection of NFT and CAP. Graphical abstract: Image 1